2012
DOI: 10.1093/fampra/cms015
|View full text |Cite
|
Sign up to set email alerts
|

Computers in the examination room and the electronic health record: physicians' perceived impact on clinical encounters before and after full installation and implementation

Abstract: Before computer installation and full EHR implementation, physicians expressed concerns about the impact of computer use on patient care. After installation and implementation, however, many concerns were mitigated. Using computers in the examination rooms to document and access patients' records along with online medical information and decision-making tools appears to contribute to improved physician-patient communication and collaboration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 22 publications
0
50
0
1
Order By: Relevance
“…For instance, some studies show EMR use can prevent doctors from focusing on patients, impede communication, and be detrimental to the patient-doctor relationship. [12][13][14][15] In order to provide patient-centered care in the digital age, it is critical to understand how EMR use impacts the quality of communication and the patient-doctor relationship.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, some studies show EMR use can prevent doctors from focusing on patients, impede communication, and be detrimental to the patient-doctor relationship. [12][13][14][15] In order to provide patient-centered care in the digital age, it is critical to understand how EMR use impacts the quality of communication and the patient-doctor relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike numerous studies qualifying this technological integration, which are often post hoc surveys, a study by Doyle et al (2012) offers a comparative pre-post approach: two sets of physician qualitative interviews conducted prior to and following the installation of computers and EHRs. This method allows for analysis of the progression of the physicians' perspectives on their interactions with patients.…”
Section: Resultsmentioning
confidence: 99%
“…Initially, Doyle et al (2012) found that physicians expressed concerns about "possible breaches of patient confidentiality" and "decreased eye contact" (p. 603-4) negatively affecting the physician-patient interaction. By the second set of interviews, concerns about privacy and confidentiality seemed to have largely dissipated and physicians felt that the EHR served as a communication and collaboration tool with patients (p. 605).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cada paciente requirió por término medio 26,9 ± 4,1 clics (mediana: 28,4 clics/paciente). No existen diferencias estadística-mente significativas entre los diferentes tipos de consulta aceptado por profesionales y por pacientes 5,6 ; sin embargo, su uso y su presencia no debe ser un elemento de alejamiento o distanciamiento en la relación médico-paciente.…”
Section: Sr Editorunclassified